IMPLIKASI PENDIDIKAN TINGGI WANITA DALAM MEMBANGUN KELUARGA SAKINAH IBU RUMAH TANGGA YANG BERPROFESI SEBAGAI GURU DI MASS TEBUIRENG JOMBANG - Anam Muhyidin; Abdullah Afif (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Education is one of the important aspects that can improve the quality of a person and strengthen his dignity in the eyes of society. Women who have a higher education background tend to be orientated towards the world of work and activities in the public sphere. In other words, a high level of education for women generally opens up opportunities for them to play an active role and contribute not only in the domestic sphere, but also in the wider public sphere.The method used in this research is qualitative. The data collection technique shows direct observation to the object of research and interviewing housewives who work as teachers.Higher education owned by housewives who work as teachers in Tebuireng Mass can have a positive impact in building a sakinah family. The knowledge, skills and religious understanding of highly educated mothers enable them to create a peaceful, harmonious and loving family. With balanced support, highly educated mothers can be role models in guiding future generations to build a sakinah family.